IMPLEMENTASI PROGRAM MAKASSAR TIDAK RANTASA (MTR) DI KECAMATAN TAMALATE KOTA MAKASSAR - Sangkala Ibsik; Muh Khaedir (Universitas Negeri Makassar, 2018)
This research method including qualitative descriptive study. The aim is (1) To determine the program in the district of Makassar not rantasa Tamalate. (2) To determine the program implementation makassar not rantasa in Kecematan Tamalate. (3 To find out what the problem is society Kecematan Tamalate in maximizing program Makassarta Not Rantasa. This research is descriptive and qualitative sample of 30 RT (informer) drawn by purposive sampling, that the sampling is done intentionally by certain criteria. The data collection dilakukuan with depth interview, observation and documentation. the results showed that, (1) Program makassar not rantasa (MTR) launched by the Mayor of Makassar has been implemented but not maximum, especially in villages mannuruki. Program MTR covers, See Garbage Grab ( LISA), Lorong Gardeng (LOOSE), community service bulk, garbage exchange rice, I and my school does not rantasa. (2) the program implementation makassar ta not rantasa in villages mannuruki namely: work devotion bulk, garbage exchange rice, I and my school not rantasa. (3) Constraints in the implementation of the program makassar not rantasa in villages mannuruki can be seen in terms of factors of public awareness is still lacking, a lack of facilities of garbage (garbage carts), the narrowness of the yard or vacant land, the lack of trash while, and drainage.